2014
DOI: 10.1039/c3tb21860k
|View full text |Cite
|
Sign up to set email alerts
|

Biscarbazolylmethane-based cyanine: a two-photon excited fluorescent probe for DNA and selective cell imaging

Abstract: We report a novel biscarbazole-based cyanine with a large Stokes shift and TPA cross-section as a light-up probe for DNA and selective TPEF cell imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 62 publications
1
39
0
Order By: Relevance
“…[21,22] Interestingly,al arger 2PAr esponse was recently observed in quadrupolar D-p-A-p-D structuresw here two diphenylamines replacedt he analogous dimethylamino lateral groups. [25,26] In our recent work, [27] ac ationic D-p-A + -p-D quadrupolar system,w here am ethylpyridinium is the central electron acceptor and dimethylamino substituentsa re the laterale lectron We report aj oint experimental and theoretical investigation of aq uadrupolar D-p-A + -p-D system,t he electron donors being diphenylamino groups and the electron acceptor being am ethylpyridinium, in comparison with the dipolar D-p-A + system.T he emission spectra of the two compounds overlap in all the investigated solvents. For example, it was recently observed that the presence of ac ationic imidazolium in push-pulli odide salts replacingt he neutrali midazole acceptora llowedh igher2 PA cross sections to be observed because of the enhancede lectron acceptors trength of the positively chargedi midazole moiety.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…[21,22] Interestingly,al arger 2PAr esponse was recently observed in quadrupolar D-p-A-p-D structuresw here two diphenylamines replacedt he analogous dimethylamino lateral groups. [25,26] In our recent work, [27] ac ationic D-p-A + -p-D quadrupolar system,w here am ethylpyridinium is the central electron acceptor and dimethylamino substituentsa re the laterale lectron We report aj oint experimental and theoretical investigation of aq uadrupolar D-p-A + -p-D system,t he electron donors being diphenylamino groups and the electron acceptor being am ethylpyridinium, in comparison with the dipolar D-p-A + system.T he emission spectra of the two compounds overlap in all the investigated solvents. For example, it was recently observed that the presence of ac ationic imidazolium in push-pulli odide salts replacingt he neutrali midazole acceptora llowedh igher2 PA cross sections to be observed because of the enhancede lectron acceptors trength of the positively chargedi midazole moiety.…”
Section: Introductionmentioning
confidence: 91%
“…[24] The employment of ionic NLO chromophores, such as for instance methylpyridinium derivatives, was found to be promising also in view of possible biological and medical applicationsb ecause of their good water solubility (generally enhanced with respect to the neutral counterparts) and biocompatibility.T hese dyes were successfully used as fluorescent probesf or highly selectivet wophoton imaging of mitochondria and DNA in living cells. [25,26] In our recent work, [27] ac ationic D-p-A + -p-D quadrupolar system,w here am ethylpyridinium is the central electron acceptor and dimethylamino substituentsa re the laterale lectron We report aj oint experimental and theoretical investigation of aq uadrupolar D-p-A + -p-D system,t he electron donors being diphenylamino groups and the electron acceptor being am ethylpyridinium, in comparison with the dipolar D-p-A + system.T he emission spectra of the two compounds overlap in all the investigated solvents. This finding could be rationalized by TD-DFTcalculations:t he LUMO-HOMOm olecular orbitals involved in the emission transition are localized on the same branch of the quadrupolars tructure that becomes the fluorescent portion,c orresponding to that of the single-arm compound.…”
Section: Introductionmentioning
confidence: 91%
“…A 3‐D model was constructed as the schematic in Figure . Prismatic β′ phases, which extend in three equivalent directions, are framed by basal LPSO structure. The interactions are also proposed by Li et al Further investigation on interphase interfaces elucidate two types of interface: the first one is a RE‐atom free gap layer, which is about 1.3 nm based on the scale of the image; the second one is redistribution of the RE‐atoms with a periodical arrangement along the interface with average gap of 1.1 nm.…”
Section: Precipitate Structurementioning
confidence: 99%
“…A sandwich shaped structure was characterized and β′ phases are framed by basal LPSO structure. Reproduced with permission . Copyright 2016, Elsevier.…”
Section: Precipitate Structurementioning
confidence: 99%
“…Salts are especially promising not only because the cationic chromophores can act as efficient electron‐withdrawing groups (A) but also for their water solubility, which is really appealing for biological and medical applications ,. Moreover, by varying the counterion accompanying an active charged chromophore, it is possible to modify crystal packing arrangements to produce polar structures showing bulk quadratic NLO effects .…”
Section: Introductionmentioning
confidence: 99%